2007
DOI: 10.1002/adfm.200700240
|View full text |Cite
|
Sign up to set email alerts
|

Red–Yellow Fluorescence Patterning of a Polymer Film Containing Phthalimido Carbamate Groups

Abstract: Bicolor fluorescent micro‐patterns in the polymer film are prepared through the use of a new group of photobase generator containing phthalimido carbamate groups. The photobase generation from phthalimide carbamates is studied by examining the changes in pH, fluorescence intensity, and photo‐crosslinking of poly(glycidyl methacrylate). The product analysis of a model compound indicates that amine groups are produced from the photolytic cleavage of the C–N bond of the phthalimide carbamate groups. A copolymer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…Self‐quenching experiments of fluorescamine‐amine adducts using alkylamines show that the maximum fluorescence intensity is observed at an alkylamine concentration of 0.1 m M , in which solution the pH value is ca. 8.3–9.0 . It's worth mentioning that the pH values of PPrC and BPrC solutions are over 8.3, which are in the self‐quenching pH value range of the alkylamine.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Self‐quenching experiments of fluorescamine‐amine adducts using alkylamines show that the maximum fluorescence intensity is observed at an alkylamine concentration of 0.1 m M , in which solution the pH value is ca. 8.3–9.0 . It's worth mentioning that the pH values of PPrC and BPrC solutions are over 8.3, which are in the self‐quenching pH value range of the alkylamine.…”
Section: Resultssupporting
confidence: 67%
“…The final concentrations are 0.6 m M for PPrC and PPhC, 1.2 m M for SPrC, and 0.1 m M for TKPrC and BPrC, respectively. The absorption band at 280–300 nm (PPrC and PPhC), 250–276 nm (SPrC), 245–310 nm (TKPrC), and 230–277 nm (BPrC) decreases upon irradiation owing to the photodecomposition of the carbamate group . Correspondingly, the band at 300–400 nm (PPrC and PPhC), 276–400 nm (SPrC), 310–400 nm (TKPrC), and 280–400 nm (BPrC) increases upon UV irradiation due to the formation of photo‐products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we reported on fluorescence imaging based on a polymeric photobase generator containing oxime–urethane groups through use of a prefluorescent dye for amino groups . Another study described a polymer containing phthalimido carbamate groups as a bicolored fluorescent imaging material . Here, we report forming various bicolored fluorescent micropatterns on a polymer film using a concurrent photobleaching reaction of anthracene groups and photobase generation of oxime–urethane groups followed by dyeing with rhodamine B (RhB) isothiocyanate using one wavelength (310 nm) photolysis.…”
Section: Introductionmentioning
confidence: 92%
“…A binary fluorescence patterned image (blue and bluish green) was fabricated using a branched‐type aromatic oxazole polymer . Red‐yellow fluorescence micropatterns have been reported using a polymeric photobase generator bearing phthalimido carbamate groups . A polydiacetylene supramolecular system that emits red, green, and blue fluorescence has been constructed .…”
Section: Introductionmentioning
confidence: 99%